SENSOR ROBOT PEMADAM API DENGAN BEBERAPA MODE OPERASI BERBASIS TEKNOLOGI DTMF, BLUETOOTH DAN GSM - Benny Suhendar; Ahmad Surahmat; Tb.Dedy Fuady (Jurnal Ilmiah Sains dan Teknologi, 2020)
In this paper, the design and development of a multiple sensor-based fire extinguisher robot is proposed and its implementation is demonstrated by a brief discussion of construction and operation. The fire extinguisher robot developed can be operated in various modes using DTMF and Bluetooth remote control as well as GSM and GPS technology. Basically, three different sensors of flame sensor, temperature sensor, and smoke sensor have been used to ensure proper fire detection. The robot can be controlled using the DTMF remote control and an Android smartphone and can be operated in three different modes. The first mode allows fully autonomous operation of the robot which can be activated by the user or by the robot itself based on the situation. The second mode is the line following mode where the robot follows a black line drawn to detect the fire and the third mode is complete manual operation using the remote control.